Macroscopic self-assembly network of encapsulated high-performance triboelectric nanogenerators for water wave energy harvesting. (June 2019) - Yang, Xiaodan; Xu, Liang; Lin, Pei; Zhong, Wei; Bai, Yu; Luo, Jianjun; Chen, Jian; Wang, Zhong Lin
Abstract: Water wave energy is one of the tremendous clean energy reserves on earth. The utilization of wave power has long been focused but at limited scope due to challenges such as cost and durability in severe ocean environment. Here, a macroscopic self-assembly network of encapsulated triboelectric nanogenerators (TENGs) is proposed for the first time for water wave energy harvesting. By a rationally designed self-adaptive magnetic joints, the network demonstrated capabilities of self-assembly, self-healing and facile reconfiguration, greatly improving the autonomy and robustness of the system. A three-dimensional electrode structure boosts the output of the TENG unit, with an average power density of 8.69 W m −3 under ideal agitations and 2.05 W m −3 in water waves, which is more than 18 times of the power of the reported ball-shell structured device despite lower agitation frequency here. The self-assembly TENG network as a robust and high-performance structure should provide a reliable route towards large-scale utilization of the water wave energy, enabling self-powered systems in ocean. Graphical abstract: Image 1 Highlights: A self-assembly strategy for networking massive distributed small TENG units is reported. The network has highly autonomous capabilities and mechanical robustness, such as self-healing and facile reconfiguration. A three-dimensional electrode structure boosts the output of the TENG, with anaverage power density of 8.69 W m -3 . The paper provides a novel strategy to construct a distributed structure that is more adaptive to severe ocean environment. The self-assembly method should be widely applicable for the fabrication of other large-scale marine structures.